STUDENTS’ DIFFICULTIES IN WRITING DESCRIPTIVE TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 1 ONOHAZUMBA - Waruwu, Sabarudi Waruwu (Universitas Nias Raya, 2023)
AbstractThis research aimedat investigating students’ difficulties and the causes in writing descriptive text. This research used qualitative research as the research method. Data collection was carried out by using two techniques of data collections, they were: students’ worksheets and the interview. The data were analyzed by using theory found by Miles, Huberman, and Saldana. The results showed that the students’ difficulties in writing descriptive text are divided into two things, such as 1) the generic structure (the identification and description), 2) language features (focus on prominent and distinctive part of the object, the use of simple present, and the use of adjective) . The causes of students’ difficulties in writing descriptive text are the limited of vocabulary, the lack of grammar understanding, and the lack of motivation and practice. Based on the results, it can be concluded that writing descriptive text is a difficult thing for students. It is suggested that writing descriptive text should be learned and taught intensively.